Символические системы и конституирование социального смысла - Бурлачук, В. (Социология: теория, методы, маркетинг, 2004)
Critical analysis of phenomenological sociology and sociology of knowledge shows that the basic constitutive mechanisms of the social world sense should be looked for not in the sphere of type schemes, as sociology of knowledge thinks, but in the sphere of basic symbolic systems (myth, tradition, authority, ritual) which are more fundamental than type ones and preserve the social world unity.